Odpowiedzi

2010-04-11T20:53:01+02:00

a)3 + 4x = 7 - 5x
5x+4x=-3+7=10x=10

b)2x-4=12x+6=2x-12x=4+6=10x+10

c) -3 ( 1 - x ) = 5 + 2 ( x + 3 )
-3-3x=5+2x+6=3x-2x=5+3=x+8
2010-04-11T20:54:23+02:00
1.
a)
3+4x=7-5x
4x+5x=7-3
9x=5/:9
x=5/9

b)
2(x-2)=3+(4x+2)
2x-4=3+4x+2
2x-4x=3+2+4
-2x=9/:(-2)
x=-4,5

c)
-3(1-x)=5+2(x+3)
-3+3x=5+2x+6
3x-2x=5+6+3
x=14


Tylko tyle wiem.. :(
2010-04-11T21:00:26+02:00
1a
4x+5x=7-3
9x=4/:9
x=4/9
b
2x-4=3+4x+2
2x-4x=3+5+4
-2x=12/:(-2)
x=-6
c
-3+3x=5+2x+6
3x-2x=5+6+3
x=14

d
x+1
----+x=3/.2
2
x+1+2x=6
3x=6-1
3x=5/:3
x=5/3
2a
(50/5-17/5):5/4=33/5:5/4=33/5X4/5=132/25=57/25
b
15%-x
100%-20,4
-----------
x=(15X20,4):100
x=3,06